The Roles of Tuan Guru Haji (TGH) Abd Rahman Al-Fathani in the Development of Islamic Education in Patani Southern Thailand - Lessy, Zulkipli; Chemo, Supean (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2019)
Rigorous research has reported reformist figures from Islamic education in Patani Thailand, such as Tuan Guru Haji (TGH) Abd Rahman al-Fathani. This paper discusses the role of TGH Abd Rahman al-Fathani in the development of Islamic education in Ma'had Tsaqafah Islamiyah Pombing Patani Southern Thailand. This study uses field studies with in-depth interviews, observation, and a literature search. The results showed a critical point that the development of Islamic education in Muassasah Ma'had Tsaqafah al-Islamiyah since its inception until now is inseparable from the work and thought innovations of Muassasah leaders with the help of elements in Muassasah's organizational structure. This illustrates the role of TGH Abd Rahman al-Fathani in the development of Islamic education by modernizing Islamic boarding schools, spreading literacy in Islamic education, conceptualizing institutional curricula, and sparking effective learning methods. Supporting factors include togetherness in managing the curriculum and teaching and learning process, adequate facilities and infrastructure, and experienced teachers. Inhibiting factors include different abilities and psychological abilities of students, low community participation, and poor management of funds.